Can petroleum jelly be used to obtain satisfactory renal ultrasound imaging? - Ras, Reuben Charles (My University, 2021)
Introduction: Ultrasound is widely used in the medical field and has also become an integral part of daily practice in urology. Ultrasound gel is the gold standard coupling medium, but it is not always readily available. Petroleum jelly (Vaseline) was proposed as an alternative coupling medium when performing renal ultrasound. Objectives: To compare renal ultrasound imaging obtained by using petroleum jelly (test) versus conventional ultrasound gel (control). To determine if petroleum jelly ultrasound imaging is adequate for clinical use. Patients: Patients aged 18 to 75 years presenting to Thelle Mogoerane Regional Hospital (TMRH) Urology OPD, volunteered and took part in the study. Patients with wounds or skin conditions affecting the flank and abdominal area were excluded. Methods: A prospective pilot study was conducted. Forty two patients had renal ultrasounds done of their left kidney, using ultrasound gel and petroleum jelly respectively. Renal ultrasound is a routine procedure in urological practice. A single ultrasonographer performed the renal ultrasounds and scored each image 1 to 3 (1-worst, 3- best) with regards to penetration, detail and total image quality. The ultrasonographer also determined which one of the paired images was better and whether the images were adequate for clinical use. Results: Ultrasound imaging adequate for clinical use was obtained in 95.24 % (n=40) of patients when using ultrasound gel and in 88.10% (n=37) patients using petroleum jelly. Vaseline produced better imaging in 28.57% (n=12) of patients. Ultrasound gel had statistically significant better mean scores (p< 0.05) in all the evaluated categories vs Vaseline: Penetration: 2.8 vs 2.6, detail: 2.6 vs 2.4 and total image quality: 2.7 vs 2.5. This statistically significant difference could be due to the small sample size. The cost of performing a renal ultrasound with Vaseline was 30% cheaper per patient (42c) compared to ultrasound gel (60c). Conclusion: Although ultrasound gel remains the gold standard coupling medium for renal ultrasound, in a setting where ultrasound gel is not available, Vaseline is a good affordable alternative to obtain renal ultrasound imaging.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine (Urology)